2015
DOI: 10.3389/fnins.2015.00462
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Decreases Cerebrovascular Responses During Rat Hindlimb Electrical Stimulation

Abstract: Repeated stress is one of the major risk factors for cerebrovascular disease, including stroke, and vascular dementia. However, the functional alterations in the cerebral hemodynamic response induced by chronic stress have not been clarified. Here, we investigated the in vivo cerebral hemodynamic changes and accompanying cellular and molecular changes in chronically stressed rats. After 3 weeks of restraint stress, the elicitation of stress was verified by behavioral despair in the forced swimming test and by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 59 publications
3
22
0
Order By: Relevance
“…Using in vivo intrinsic imaging, we observed that ION ligation induced a decreased haemodynamic response to vibrissae stimulation in the S1BF cortex. This result is consistent with a reduced haemodynamic responsiveness of the primary sensory cortex previously reported in a model of chronic stress and triggered by enhanced iNOS and decreased nNOS and HO-2 expression [67]. However our result was unexpected, since a previous voltage-sensitive dye imaging study had described an increased neuronal response in the primary somatosensory cortex of sciatic nerve-ligated rats, with an enlarged area of activation following electrical stimulation of the hind paw [41,68].…”
Section: Discussionsupporting
confidence: 92%
“…Using in vivo intrinsic imaging, we observed that ION ligation induced a decreased haemodynamic response to vibrissae stimulation in the S1BF cortex. This result is consistent with a reduced haemodynamic responsiveness of the primary sensory cortex previously reported in a model of chronic stress and triggered by enhanced iNOS and decreased nNOS and HO-2 expression [67]. However our result was unexpected, since a previous voltage-sensitive dye imaging study had described an increased neuronal response in the primary somatosensory cortex of sciatic nerve-ligated rats, with an enlarged area of activation following electrical stimulation of the hind paw [41,68].…”
Section: Discussionsupporting
confidence: 92%
“…Summarily, chronic restraint stress decreased hemodynamic response to forelimb stimulation. Moreover, these results obtained with a mouse model are consistent with our previous work using a rat model of chronic restraint stress, which also showed reduced hemodynamic response to sensory stimuli (Lee et al, 2015).…”
Section: Reduced Hemodynamic Response To Forelimb Stimulation In Chrosupporting
confidence: 92%
“…Chronic restraint stress is a well-established protocol that induces anxiety-like behaviors in mice (Buynitsky and Mostofsky, 2009;Lee et al, 2015Lee et al, , 2018. The EPM, which contains both closed and open arms, is used to test the level of anxiety-like behaviors in animal subjects: the longer the time spent in the closed arms, the higher the level of anxiety-like behavior.…”
Section: Validation Of the Mouse Chronic Stress Modelmentioning
confidence: 99%
See 2 more Smart Citations